Stroke-like presentation of toxic leukoencephalopathy as the initial manifestation of HIV infection - Reuter, Björn; Wolf, Marc; Förster, Alex; Kalvin, Kira; Szabo, Kristina; Bäzner, Hansjörg; Hennerici, Michael G. (Case reports in neurology, 2012)
The toxic leukoencephalopathy syndrome is increasingly recognized, but rarely presents as an acute cerebrovascular syndrome. We report a 23-year-old man with sudden onset of a right hemispheric sensorimotor syndrome and final diagnosis of HIV-induced toxic leukoencephalopathy.
Gesehen am 28.05.2018